A Study of Comparison Between Expressing and Existing Halting Patterns in the Korean High Speed Railway - Kim, Do Kyung; Jung, Jihye; You, Soyoung Iris; Yu, Jeongwhon; Oh, Suk Mun (Journal of the Korean Society for Railway, 2024)
In this paper, we present results of comparison between existing and expressing halting patterns for the Korean High Speed Railway (HSR). To get optimal halting patterns, we formulate an optimization model (LPP-HSR-EXPRESS) in a pure Integer Programming model. We present a set of optimal solutions of the model and results of comparison to the existing halting patterns. We got a set of near optimal solution with less than 0.25% of the optimality-gap. The optimal solution consists of 118 different halting patterns, which is 83% of the existing patterns (144 patterns). Moreover, the optimal patterns yield 4.0% saved total travel time compared to the case of existing patterns. The 4.0% reduction in total travel time provides margin for additional express HSR to be introduced without compromising total travel time compared to existing operation method. This shows the possibility of reducing travel time for customers who choose express HSR without losing total travel time.
Keywords: Express; Halting pattern; HSR; Line-planning; Operation